Species-specific responses in pigments and fatty acids of five freshwater chlorophytes exposed to varying cultivation conditions. (January 2022) - Parkes, Rachel; Barone, Maria Elena; Aranyos, Anita; Fierli, David; Koehler, Henry; Gillespie, Eoin; Touzet, Nicolas
Graphical abstract: Highlights: Five freshwater chlorophytes were exposed to varying cultivation conditions. Molinate supplementation enhanced carotenogenesis in Kirchneriella sp. The highest cellular content of lutein (4.9 mg. g −1 ) was found in Kirchneriella sp. The highest cellular content of β-β-carotene (4.7 mg. g −1 ) was found in Ankistrodesmus sp. Only Chloromonas sp. contained EPA, the highest content being returned via phytohormone supplementation (2.6 mg. g −1 ). Abstract: Microalgae have attracted increasing interests within several industrial sectors. Their diversity, underpinned by complex polyphyletic origins, represents an under-exploited source of high-value metabolites. Five freshwater chlorophytes ( Ankistrodesmus sp., Pediastrum sp., Kirchneriella sp., Chloromonas sp. and Scenedesmus sp.) were grown under varying cultivation conditions including high nitrate supply, phytohormone supplementation, exposure to the herbicide molinate and exposure to blue LED light. When exposed to molinate (2.5 μg. mL −1 ), Kirchneriella sp. returned the highest lutein cellular content (4.9 mg. g −1 ). Zeaxanthin production (4.1 mg. g -1 ) was also highest for Scenedesmus sp. when molinate was introduced to the cultivation medium. Only Chloromonas sp. contained eicosapentaenoic acid (EPA), which returned the highest cellular content (2.6 mg. g −1 ) when the culture was supplemented with the phytohormone indole-3-acetic acid (2.5 μg. mL −1 ). Scenedesmus sp. showed an increase in the proportions of alpha-linolenic acid (∼55 %) when grown in medium enriched in nitrate. Overall, molinate supplementation enhanced the accumulation of lutein, β-β-carotene and chlorophyll a in Kirchneriella sp. These chlorophytes showed a species rather than treatment-specific response with regards to pigment cellular contents and fatty acid profiles, re-enforcing the notion that the optimisation of intracellular contents of valuable metabolites as part of a tailored biorefinery strategy needs to be considered at the species level.